The Interaction Between Nitrogen Supply and Light Quality Modulates Plant Growth and Resource Allocation - Liang, Ying; Cossani, C. Mariano; Sadras, Victor O.; Yang, Qichang; Wang, Zheng (Frontiers in Plant Science, 2022)
Nitrogen availability and light quality affect plant resource allocation, but their interaction is poorly understood. Here, we analyzed the growth and allocation of dry matter and nitrogen using lettuce (Lactuca sativa L.) as a plant model in a factorial combining three light regimes (100% red light, R; 50% red light + 50% blue light, RB; 100% blue light, B) and two nitrogen rates (low, 0.1 mM N; high, 10 mM N). Red light increased shoot dry weight in relation to both B and RB irrespective of nitrogen supply. Blue light favored root growth under low nitrogen. Allometric analysis showed lower allocation to leaf in response to blue light under low nitrogen, and similar leaf allocation under high nitrogen. A difference of allometric slopes between low nitrogen and high nitrogen in treatments with blue light reflected a strong interaction effect on root-to-shoot biomass allocation. Shoot nitrate concentration increased with light exposure up to 14 h in both nitrogen treatments, was higher under blue light with high nitrogen, and varied little with light quality under low nitrogen. Shoot nitrogen concentration, nitrogen nutrition index and shoot NR activity increased in response to blue light. We conclude that the interaction between blue light and nitrogen supply modulate dry mass and nitrogen allocation between shoot and root.